How to develop business information systems for end users - Garland, John L. (John Wiley New YorkUS, 1986)
Describes evolution of business information systems (BIS). Identifies major categories of end user BIS currently available. Shows how to organize, plan and implement systems supporting business measurements, planning and analysis. Discusses ways of ensuring that the BIS is focusing on the proper goals and that the hardware and software are adaptable to changing business needs. Presents methodology for establishing business value of a proposed information system investment. Shows how to organize and treat data as a multi-use business asset and how to use programming skills to solve business problems. Identifies approach for selecting commercial software, for developing service level agreements and for measuring efficiency of a BIS.